Improving shared decision making for lung cancer treatment by developing and validating an open-source web based patient decision aid for stage I–II non-small cell lung cancer - Halilaj, Iva; Ankolekar, Anshu; Lenaers, Anouk; Chatterjee, Avishek; Oberije, Cary J. G.; Eppings, Lisanne; Smit, Hans J. M.; Hendriks, Lizza E. L.; Jochems, Arthur; Lieverse, Relinde I. Y.; van Timmeren, Janita E.; Wind, Anke; et al. (Frontiers in Digital Health, 2024)
The aim of this study was to develop and evaluate a proof-of-concept open-source individualized Patient Decision Aid (iPDA) with a group of patients, physicians, and computer scientists. The iPDA was developed based on the International Patient Decision Aid Standards (IPDAS). A previously published questionnaire was adapted and used to test the user-friendliness and content of the iPDA.The questionnaire contained 40 multiple-choice questions, and answers were given on a 5-point Likert Scale (1-5) ranging from "strongly disagree" to "strongly agree." In addition to the questionnaire, semistructured interviews were conducted with patients. We performed a descriptive analysis of the responses. The iPDA was evaluated by 28 computer scientists, 21 physicians, and 13 patients. The results demonstrate that the iPDA was found valuable by 92% (patients), 96% (computer scientists), and 86% (physicians), while the treatment information was judged useful by 92%, 96%, and 95%, respectively. Additionally, the tool was thought to be motivating for patients to actively engage in their treatment by 92%, 93%, and 91% of the above respondents groups. More multimedia components and less text were suggested by the respondents as ways to improve the tool and user interface. In conclusion, we successfully developed and tested an iPDA for patients with stage I-II Non-Small Cell Lung Cancer (NSCLC).